Ocular manifestations of a metastatic adenocarcinoma in a horse. (5th July 2012) - Matheis, Franziska L.; Birkmann, Katharina; Ruetten, Maja; Pot, Simon A.; Spiess, Bernhard M.
Abstract: A 10‐year‐old German Warmblood gelding was referred to the Equine Department of the Vetsuisse Faculty, University of Zurich, Switzerland, for an iris mass OD, lethargy, intermittent fever, and coughing. Ophthalmic examination revealed a 7 × 9 mm raised, fleshy, whitish to pinkish, vascularized iris mass at the 2 o`clock position OD. Fundic examination showed multifocal round, brown to black, slightly raised lesions with indistinct margins and a surrounding hyperreflective zone OU. Physical examination revealed a temperature of 39.2 °C, sinus tachycardia, preputial and ventral edema, and an enlarged right mandibular lymph node. Results of a complete blood count and plasma biochemical profile showed mild anemia, leukocytosis, and thrombocytopenia. Severe splenopathy, moderate splenomegaly, and severe pulmonary pathology with nodules and large areas of consolidated lung parenchyma were observed on abdominal ultrasound and thoracic radiographs, respectively. Fine needle aspirates of the enlarged mandibular lymph node showed malignant epithelial neoplastic cells. The horse was euthanized because of the poor prognosis and subsequently underwent postmortem examination. Macroscopic necropsy and histopathology revealed an adenocarcinoma of suspected pulmonary origin with involvement of eyes, heart, liver, kidneys, spleen, diaphragm, skeletal muscles, mandibular, pulmonary, and internal iliac lymph nodes. Metastatic adenocarcinoma should be considered as a differential diagnosis in horses with iris masses, multifocal chorioretinal infiltrates, and clinical signs that conform to a paraneoplastic syndrome.